INAF-UC Berkeley collaboration on SETI activities - Melis, A.; Maccone, C.; Pilia, M.; Siemion, A.; Perrodin, D.; Enriquez, J.; Antonietti, N.; Werthimer, D.; Concu, R.; Hellbourg, Gregory; Montebugnoli, S.; Pari, P.; et al. (2018)
No Abstract Available